Implementasi Nilai Al-Islam dan Kemuhammadiyahan: Studi Mahasiswa Non-Muslim di Universitas Muhammadiyah Sorong - Ali, Muhammad; Wirawan, Muhammad; Kamaluddin, Kamaluddin; Mardliyah, Uswatul; Basri, La (Universitas Muhammadiyah Sorong, 2023)
This research aims to analyze the implementation of Al-Islam and Muhammadiyahan values ​​in non-Muslim students at Muhamamdiyah University, Sorong, which is based on the Al-Islam and Muhammadiyahan courses given by all students, not only Muslim but also non-Muslim, for 4 semesters (I, II, III and VII). Qualitative methods as data analysis using observation, interview and literature study data collection methods. Data collection was carried out on course lecturers and non-Muslim students from various study programs. The research results show that AIK teaches non-Muslim students about the good values ​​of tolerance, ethics, morals and morals. When you meet a lecturer, kiss each other's hands, say